On the generalized blaschke condition - Chee, P.S. (American Mathematical Society, 1970)
In an earlier paper, the author has shown that the generalized Blaschke condition is satisfied by bounded holomorphic functions in the polydisc or the ball in CN. By essentially the same method, it is shown in the present paper that the same condition is satisfied by larger classes of functions, the Nevanlinna classes. © 1970 American Mathematical Society.